Pengaruh Total Quality Management Terhadap Kinerja Manajerial Pusat Kesehatan Masyarakat Di Kabupaten Boyolali - Harjani, Sri, Drs. Muhammad Abdul Aris, M.Si (2016)
This study aims to determine the effect of Total Quality Management to managerial performance of Community Health Centers in Boyolali. Based on the results of the study are expected to know the factors that influence managerial performance in managing the community health center in Boyolali, so it can apply the right strategy to further enhance the patient's behavior in making use of public health services in Boyolali. The design of this study survay done by taking a sample of a population in a real environment. The population in this study are all head or the head of the community health center in Boyolali of the 36 respondents. The research sample is taken based on census methods that make the whole population into research data, so that the sample in this study amounted to 36 respondents. The analytical tool used in this research is multiple linear regression. Based on the survey results revealed that the effect of customer focus on managerial performance values obtained tcount of 2.679 with p = 0.012 < 0.05; then H1 accepted, meaning that the focus on the customer significant effect on managerial performance of the managerial staff or the head of the community health center in the district of Boyolali. Effect of continuous improvement on managerial performance values obtained tcount of 2.127 with p = 0.041 < 0.05; then H2 is accepted, which means that continuous improvement significant effect on managerial performance of the managerial staff or the head of the community health center in the district of Boyolali. Effect of employee empowerment on managerial performance values obtained tcount of 2.978 to 0.05 p = 0.005; the H3 is received, which means that the employee empowerment significant effect on managerial performance of the managerial staff or the head of the community health center in the district of Boyolali. Keywords: total quality management, managerial performance